The Hydrothermal Synthesis of ZnO-CdO Composite and Physical and Electrical Characterization - Canbay, Canan Aksu; Biro, Safiye Jameel; Özkul, İskender (Batman Üniversitesi, 2018)
In this study, ZnO-CdO composites were synthesized by hydrothermal method. Two different contents of the nano-composites have been fabricated for the investigation of structural, morphological, optical and electrical properties. X-ray diffraction (XRD), FTIR, scanning electron microscopy (SEM), UV-VIS-NIR spectrophotometer and two probe methods were used for these analyses. At the same time, the chemical analysis of the sample was measured by EDX analysis. The TG-DTA analyses were made to determine the thermal stability. The optical band gap of composites was found to be 2.78 and 3.06 eV, respectively, with an increase in the content of the Zn precursor.
Keywords: Engineering; Mühendislik